Pengaruh Bangkitan Penggunaan Lahan Terhadap Kinerja Ruas Jalan (Studi Kasus : Jalan Soekarno Hatta KM. 4-5) - Nissa, Tiara; Hidayat, Arief; Arif Nugroho, Rizky; Putra, Rulliannor Syah (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Transportation and land use planning are two interrelated aspects. A mismatch between land use regulations and an unaligned transportation system will trigger various transportation issues, such as congestion. The higher the level of land use generation, the higher the traffic volume on a road. One of the road corridors with a high intensity of vehicle movement generation in Balikpapan is the Soekarno-Hatta KM 4-5 road corridor. The purpose of this study is to examine whether the movement generation caused by the existing land use in the area affects the road performance on the Soekarno-Hatta KM 4-5 Corridor in Balikpapan City. The data collection method uses primary surveys to determine the influence of land use generation on road performance in the study location, using the trip-rate method. The findings reveal that most of the land use along the corridor falls into the category of having a minor impact; two land uses have a moderate impact, and one land use significantly affects the road performance in the area, which is the use of the Platinum Hotel.